Possibilities of vitamin-mineral complexes in adjuvant therapy of comorbid patients with periodontal diseases, diabetes and other systemic diseases of the body - Dmitry I. Trukhan; Anatoly F. Sulimov; Larisa Yu. Trukhan (LLC "MEDIAFORMAT", 2024)
Periodontitis is a disease of the dental system, characterized by the development of an acute or chronic inflammatory process, destruction of periodontal tissue and atrophy of the bone tissue of the alveoli. Periodontitis is the sixth most common disease in the world and the leading cause of tooth loss in adults. The attention of internists to the problem of periodontitis and periodontal diseases is associated with the concept of "periodontal medicine," which was formed at the beginning of the 21st century, and considers the bidirectional connection of periodontal pathology with systemic diseases of the body. Nutritional status is now widely recognized as a possible contributing factor in the development of many inflammatory conditions such as periodontal disease. We searched for publications devoted to the study of the influence of microelements selenium, zinc, vitamins A, E, C on the physiology and pathology of periodontal disease. The search was carried out in the PubMed and Scopus information databases; sources up to March 31, 2024 were included. The data presented in the review indicate a deficiency of the microelements selenium, zinc and vitamins A, C, E in periodontitis and suggest the advisability of their correction as part of the adjuvant therapy of periodontal diseases. A number of studies reviewed noted that increased levels of microelements and vitamins lead to clinical improvement in periodontal health. The most pronounced deficiency of microelements and vitamins is observed in patients with periodontitis in the presence of concomitant diabetes mellitus.